Green Synthesis of Silver Nanoparticles using Cirsium congestum Extract Modified by Chitosan/Alginate: Bactericidal Activity against Pathogenic Bacteria and Cytotoxicity Analysis in Normal Cell Line - Mohtashami, Mahnaz; Rezagholizade-Shirvan, Alieh; Hojati Bonab, Zahra; Amiryousefi, Mohammad R.; Darroudi, Majid; Ahmadi Solimani, Mobina Sadat; Yaghoobi, Sajad; Dolatabadi, Samaneh; Ghasemi, Ahmad; Momtazi-Borojeni, Amir Abbas (Current Pharmaceutical Design, 2024)
Aim: The study aimed to determine in vitro pharmacological effects of modified Ag nanoparticles (AgNPs). Background: AgNPs are considered antimicrobial agents. However, the cytotoxicity of chemically synthesized AgNPs (cAgNPs) has raised challenges that limit their use. Objective: The purpose of the study was to examine the antimicrobial and cytotoxicity effects of AgNPs synthesized using Cirsium congestum extract modified by chitosan/alginate AgNPS (Ch/ALG-gAgNPs). Methods: Nanoparticles were characterized using TEM, DLS, XRD, and FTIR. Resistant strains of Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) were used for the antimicrobial analysis of Ch/ALG-gAgNPs using disc diffusion and microdilution methods. The effects of NPs on cell viability and apoptosis in L929 normal cells were determined using MTT assay and annexin/PI staining, respectively. Results: Physicochemical characterizations confirmed Ch/ALG-gAgNPs to be spherical and uniformly dispersed, and their size ranged from 50 to 500 nm. Ch/ALG-gAgNPs inhibited the growth of microbial strains in a dose-dependent manner. The antibacterial effect of Ch/ALG-gAgNPs was significantly higher than cAgNPs. The Ch/ALG-gAgNPs showed little cytotoxicity against normal cells at concentrations less than 50 μg/ml. Cytotoxicity effects of Ch/ALG-gAgNP were less than cAgNPs. Flow cytometry and real-time PCR results showed a decrease in apoptosis percentage and BAX marker in the presence of Ch/ALG-gAgNPs relative to when the cell was treated with cAgNPs. Conclusion: Current findings introduce novel gAgNPs modified with chitosan/alginate for use in medicine.
Keywords: chitosan